Comparative modal analysis of B70 and LCR-6 type railway sleepers after repeated impact loads. (20th June 2022) - Çeçen, Ferhat; Aktaş, Bekir; Öztürk, Hakan; Öztürk, İrfan Ş.; Burhan Navdar, M.
Highlights: Railway sleepers were subjected to 50-times repeated impact loading. Pre-stressed and LCR sleepers were investigated comparatively before and after impacts. This is the first study to compare new LCR-6 type sleepers after impact loads. LCR-6 type sleepers' modal damping values are 274% better. LCR sleepers' hairline cracks don't cause significant capacity loss. Abstract: Due to today's high-frequency trainloads and wheel or rail irregularities, the railway system is more exposed to impact loading conditions. In this study, laminated carbon fiber reinforced polyurethane (L-CFRPU) products were used, with a new non-pre-stressed production process, to improve the impact damping characteristics of concrete railway sleepers. New designed LCR-6 type sleepers were compared with standard B70 type pre-stressed concrete sleepers by performing modal analysis before and after a 50 times repeated-330 kN impact loading procedure. This is the first study to compare new LCR-6 type sleepers with prestressed competitors after impact loads. According to the analysis results, FRF magnitude values ​​decrease up to 83% lower in impacted LCR-6 type sleepers compared to impacted B70 type sleepers. After the impact loading procedure, the cracks formed in LCR-6 type sleepers closed and remained below 50-µm width, and according to the simultaneous mechanical test results, these few hairline cracks do not cause a significant mechanical capacity loss, while increasing the damping ratios by 274%. This advantage will be beneficial in extending the service life of sleepers and protecting other railway components from vibration and impact damage. Therefore, while the pre-stressed concrete sleepers have a negative course during their service life, the non-pre-stressed LCR type sleepers show a positive acceleration.